Pengaruh Kemudahan, Kepercayaan dan Keamanan terhadap Keputusan Penggunaan Mobile Banking BCA di Jakarta - Annisa Rizky Widodo; Fajri Ariandi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
With the increasingly rapid development of information technology, people need to do things quickly, effectively and efficiently, especially when carrying out transaction activities. Banking companies are improving services with the introduction of mobile banking. Mobile banking is an innovation from development, science, information technology and communications used by banking companies to facilitate customer transactions and meet needs, which can be accessed by installing an application on the phone. BCA Bank is a private bank that offers digital banking services, one of which is a mobile banking product known as BCA mobile, launched in 2011. By providing banking services via smartphone. BCA bank hopes that customers can enjoy the convenience and speed of BCA Mobile. The aim of this research is to determine the influence of convenience, trust and security on decisions to use mobile banking in Jakarta. The method used in this research is non-probability sampling, namely purposive sampling. The data collection technique was through distributing questionnaires to 100 respondents and processed using SPSS version 25. The analysis method used was multiple linear regression. The results of the hypothesis test show that the variables of ease, trust and security have a significant effect on usage decisions.